Proceedings of the 9th European Conference on Interactive TV and Video 2011
DOI: 10.1145/2000119.2000145
|View full text |Cite
|
Sign up to set email alerts
|

Field trial of a dual device user experience for iTV

Abstract: With the rise in highly capable, mobile and networked secondary devices, the two-screen Enhanced TV is a more plausible proposition today than ever before. This paper presents a field trial of a prototype that aimed to understand a conceptual merger of TV and second screen user experiences. Our prototype concept can be described as a companion device experience that enhances TV viewing by providing auxiliary information and media on a second screen. The additional media is semantically related and synchronized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 10 publications
(5 reference statements)
3
25
0
Order By: Relevance
“…Participants also liked not having to search for information online (2 of 18), and the "filling in" during quieter parts of the programme (7 of 18). These are like the findings of previous research [1,8,24]. The remaining 10 participants, however, said they would not use it again, citing their preference to focus on the TV (4 of 18), and their dislike of having to switch to another device (5 of 18).…”
Section: Interview Findingssupporting
confidence: 77%
See 1 more Smart Citation
“…Participants also liked not having to search for information online (2 of 18), and the "filling in" during quieter parts of the programme (7 of 18). These are like the findings of previous research [1,8,24]. The remaining 10 participants, however, said they would not use it again, citing their preference to focus on the TV (4 of 18), and their dislike of having to switch to another device (5 of 18).…”
Section: Interview Findingssupporting
confidence: 77%
“…These have included systems that increase accessibility to disabled users [24], and add synchronized companion content to the main program [1]. Users reacted positively to the availability of additional information without needing to look it up themselves.…”
Section: Related Work Tv Companion App Experiencesmentioning
confidence: 99%
“…Another avenue of exploration has looked at support for social second screeners through dedicated apps. For example, early work by Regan and Todd [37] on instant messaging in a media centre, has more recently been extended by systems which allow people to share and communicate while watching TV; to become further engaged with their programmes, both when co-located [3,29] and distributed [6].…”
Section: Second Screening and Cross-device Experiencesmentioning
confidence: 99%
“…For instance, we are poorly cognitively equipped to deal with simultaneous reading and listening [39]. Deployments and empirical investigations of dual-screen scenarios have suggested that additional cognitive load is introduced when compared to traditional TV use: Basapur et al [6] note in their deployment of a companion system that users considered this 'active' TV, and not necessarily something one would unwind to. Such findings were also observed by Geerts et al [17], who noted that viewers had to manage a good balance between engagement and distraction with the second screen application, and return to some details in the application later (i.e., when the TV material was no longer relevant).…”
Section: Dual-screen Attention: Hinderances and Enhancementsmentioning
confidence: 99%
“…Increasingly, users are bringing mobile computing devices into the living room whilst watching television, using them as a second screen. Multiscreen applications, bespoke second screen experiences that augment and enhance programming with additional content, are one mechanism by which viewers consume synchronously between TV set and mobile computing device [5]. At the same time, the rise of user-generated video is bringing "traditional notions of the 'amateur' and 'professional' into question" as amateur content is an increasingly important part of media production and consumption [21].…”
Section: Introductionmentioning
confidence: 99%